Problems in periorbital surgery a repair manual - Nahai, Foad, 1943-; Wojno, Ted H. (Thieme, 2019)
"The field of periorbital surgery has expanded exponentially in recent decades. With its rise in popularity, however, comes a rise in complications. Finally there is a comprehensive guide to repairing the problems encountered in periorbital surgery, compiled by masters in the art of periorbital surgery! This unique resource for plastic, facial plastic and oculoplastic surgeons offers several key features: - A thorough discussion on the history and examination for the evaluation of the eyelid - Stepwise guidance for correcting a range of complications in periorbital surgery, including infection and bleeding, blindness and motility disorders, specific upper and lower eyelid problems including lid retraction, chemosis, and adverse results from fillers and resurfacing - Several chapters, presenting different approaches, devoted to the challenging problem of lid retraction and its multifactorial etiology - A case-report format that provides detailed discussions of all possible complications - Expert techniques from renowned surgeons providing multiple perspectives on the same problems - More than 300 color photographs and beautifully detailed surgical illustrations - Multiple video clips showing details of eyelid evaluation and corrective techniques - Both print and electronic formats for easy access everywhere To meet the ever-increasing patient demand for these youth-restoring procedures, all surgeons undertaking eyelid surgery and committed to prevent and treat complications of periorbital surgery should have this resource in their collection! Foad Nahai, MD, FACS, FRCS (HON), Maurice"--Provided by publisher.